INTERAKSI MIKROALGA-BAKTERI DAN PERANANNYA DALAM PRODUKSI SENYAWA DALAM KULTUR MIKROALGA - Diah Radini Noerdjito (OSEANA, 2019)
MICROALGAE-BACTERIA INTERACTIONS AND THEIR ROLES ON METABOLITES PRODUCTION OF MICROALGAE CULTURE. During this time, bacteria existence in microalgae culture is considered as a negative thing. Recently, the interaction between bacteria and microalgae can also be a mutually beneficial relationship or not detrimental to the other party. The mutually beneficial relationship between bacteria and microalgae can be applied as basic knowledge to increase microalgae culture production, which can be used further as a control mechanism for bacterial-microalgae interactions and can help increase the biomass production and certain metabolites microalgae culture. Another application is such as in environmental technology for bioremediation and bloom control.